Advancing Reproductive Justice to Close the Health Gap: A Call to Action for Social Work. Issue 4 (6th October 2020) - Gomez, Anu Manchikanti; Downey, Margaret Mary; Carpenter, Emma; Leedham, Usra; Begun, Stephanie; Craddock, Jaih; Ely, Gretchen
Abstract: Reproductive justice is an intersectional social movement, theory, and praxis well aligned with social work's mission and values. Yet, advancing reproductive justice—the right to have children, to not have children, to parent with safety and dignity, and to sexual and bodily autonomy—has not been a signature area of scholarship and practice for the field. This article argues that it is critical for social work to advance reproductive justice to truly achieve the grand challenge of closing the health gap. The article starts by discussing the history and tenets of reproductive justice and how it overlaps with social work ethics. The authors then highlight some of the ways by which social workers have been disruptors of and complicit in the oppression of individuals, families, and communities with regard to their reproductive rights and outcomes. The article concludes with a call to action and recommendations for social work to foreground reproductive justice in research, practice, and education efforts by centering marginalized voices while reimagining the field's pursuit of health equity.